Optical fiber based environmental sensors - Huang, Jieyuan (2016)
Optical fiber-based refractive index (RI) sensors have widespread applications in the fields of chemical and biomedical sciences and their sensing capabilities can be enhanced by depositing various materials. Carbon nanotubes (CNTs), as one of these feasible materials, have found much potential in the enhancement of RI sensing and analyte detection. This thesis includes the basic CNT deposition for fiber optic sensors, design and fabrication of improved optical refractive index sensors, and the corresponding sensitivity achieved. The significance of the study is to use CNTs for measurement, sensitivity enhancement and other benefits. In this thesis, we will describe the investigation of the deposition of CNTs onto a specifically designed joint fiber end by means of optical deposition. The joint fiber end consists of a standard single-mode fiber (SMF) and a multi-mode fiber (MMF) segment with certain length. A tunable laser and an erbium-doped fiber amplifier (EDFA) were used as a power source and CNTs were deposited at the end of the fiber due to gradient force. Owing to the fiber-film reflectance expression, the intensity of light reflected by the fiber end face will change with the variation of the external refractive index of the ambient environment. In our refractive index sensing experiment, the fabricated fiber sensor head is probed into prepared sugar solutions with different concentrations with refractive index ranging from 1.33 to around 1.46. The RI sensing is registered with the intensity change of the optical spectrum of reflected light measured by an optical spectrum analyzer (OSA), and a maximum sensitivity of 29.3 dB/RIU for the fabricated fiber sensor is achieved. This CNT-deposited SMF-MMF joint fiber environmental sensor achieves a relatively good RI sensitivity within the measurement range, compared to other fiber sensors combining with CNTs and graphene deposition. In addition, using CNTs as part of the sensing element can extend the RI measurement range to as high as the RI value of CNTs.